A Interpretação de Intervenção Jurisdicional no Orçamento Público: Concretização dos Direitos Fundamentais à saúde e à Educação - Mendes, Ana Araújo Ximenes Teixeira (2008)
The purpose of this work is to analize the interpretation of the brazilian Judiciary concerning lawsuits which clame intervention in the public budget with a view to accomplishing fundamental rights to health and education, as well to evaluate the suitability of such interpretation to the principles of the New Hermeneutics. For this objective, we first outlined the evolution occurred in Hermeneutics, in order to distinguish the New from the Classical Hermeneutics and provide an approximate view of the New Hermeneutics, making possible the realization of how it reflects on the interpretation of the Federal Constitution and the fundamental rights. Analizing critically the jurisprudence in focus, the research have given emphasis to the study of the ideological element that is underlying in any interpretation, stressing the need to subject it to criticism in comparison with the ideology within the constitutional text, wich is part of the limits of the legal discourse and should prevail over the interpreter’s ideology. In this task, we have identified the conception relating to the principle of separation of powers as a determining factor to the course taken by the brazilian Judiciary interpretation regarding the legal actions for the accomplishment of the fundamental rights to health and education in their coletive sense through intervention in the public budget, which made necessary to analize specifically the principle of separation of powers, discoursing upon the necessity of its compability with the principle of the State of Law. This work also emphasizes the vital importance of the Attorney General’s Office in these legal actions, clarifying that it integrates the checking system (checks and balances system) instituted by the Federal Constitution through the principle of separation of powers, so that its presence as suiter – by the link with the principle of separation of powers that the institution possesses – is a major factor to be considered in the interpretation of the lawsuits which clame intervention in the public budget with a view to accomplishing fundamental rights to health and education.